Anticancer activity of ginsenosides Rh2 on various cancer cells - Seun Eui Kim; Myoung-Hoon Lee; Hye-Myoung Jang; Wan-Taek Im; Joontaik Lee; Sang-Hwan Kim; Gwang Joo Jeon (The Korean Society of Animal Reproduction and Biotechnology, 2023)
Background: This study has mainly focused on finding pharmacological effects of ginsenosides that can reduce the unwanted side effects of the cytotoxic anticancer drugs and are highly effective on prostate cancer, colorectal cancer, liver cancer, hormone-dependent breast cancer, triple-negative breast cancer, and brain cancer (neuroblastoma). Methods: Minor and rare ginsenosides (GS) of Rh2 which have a high absorption ability and excellent pharmacological actions were treated with the 6 different types of cancer cell lines and their anticancer activities were investigated by analyzing gene expressions associated with various cancers through qPCR and other relevant methods. Results: In cancer cells exposed to Rh2, cell viability and cell migration were reduced, and apoptosis was induced. Each cancer cell was divided into three groups according to the cell proliferation response by Rh2; 1) A group in which the cell viability decreases inversely to an increase in Rh2 treatment concentration; 2) A group in which the cell viability rapidly decreases in Rh2 treatment above a certain level of concentration; 3) A group in which the cell viability was not suppressed below 20-30% even with 100 μL of Rh2, the highest concentration used in this study. Conclusions: It was shown that Rh2 has a significant effect on inhibiting the proliferation of prostate cancer cells and hormone-dependent breast cancer cells.